SEKOLAH ADIWIYATA DALAM DIMENSI KARAKTER DAN MUTU PENDIDIKAN - Rizki Nur Aprilianto; Ardian Arief (Universitas Sarjanawiyata Tamansiswa, 2019)
The Adiwiyata Program is an effort to create schools that innovate in science and the environment. Besides, to encourage the creation of knowledge and awareness of school residents to take responsibility for preserving a clean and healthy environment. Schools are also required to provide innovative ideas in their role as educational institutions that care for the environment. Schools must provide examples and benchmarks for creating a clean and healthy environment. The Adiwiyata program is an environmental education program that greatly supports the achievement of graduate standards in schools, with the development of character accustomed to this Adiwiyata school program through its three principles, namely educative, participatory, and sustainable. The Adiwiyata program can bring awareness to all parties about caring for the environment. Much can be done in schools in the context of environmental education.